Pengembangan Media X-Box untuk Meningkatkan Pemahaman Siswa Sekolah Dasar tentang Perkalian - Kristiningrum Kristiningrum (Jurnal Didaktika Pendidikan Dasar, 2020)
This learning innovation work was created based on the finding that students in primary schools still have difficulty in multiplication operations of up to four digits. There is no use of innovative media in learning that can be used effectively for multiplication learning. The making and use of X-boX media is to make it easy for students to understand and be proficient in performing multiplication calculation operations. The method used in this study is the design and development (D&D) by testing using tests given to students and design validation by experts. Obtained results of media validation by 94% and material validation by 82%. Experts claim that this innovation work is in the good category and is suitable for use in learning about multiplication. Based on the results of the reflection made, the X-boX media was considered effective in increasing student understanding. Evidenced by the average value of student learning outcomes that are above the KKM value after testing.